Gregorio Correr, James Calfhill, and the Early Elizabethan Affordances of Senecan Tragedy. (March 2020) - Perry, Curtis
Abstract : This essay re-examines the relationship between James Calfhill's lost play Progne, which was performed before Queen Elizabeth at Oxford University in 1566, and Gregorio Correr's (or Corraro's) fifteenth-century neo-Senecan tragedy Procne . It argues that Calfhill likely based his play closely upon Correr's, which had been printed by Paulo Manuzio for the Academia Venetiana in 1558. In addition to considering how and why a play based on Correr's Procne might have been chosen for performance before Elizabeth at Oxford, the essay argues that the possible existence of such a play should prompt reconsideration of the affordances of early Elizabethan Senecan tragedy more generally. Correr's play, it is proposed, is an exceptionally sophisticated study of Senecan characterization, and locating a play based closely upon it within the context of early Elizabethan Senecan imitation casts new light on the question of how Senecan tragedy was taken up in England.